Description of a new species of Cylloepus Erichson from southeastern Brazil (Coleoptera, Elmidae) - Passos,Maria Inês Silva (2004)
Cylloepus dorvillei sp. nov. is described and illustrated from a first order stream at the Atlantic Forest in Rio de Janeiro State, Brazil. Taxonomic and habitat notes on the new species are presented.